The Impact of an Antimicrobial Stewardship Clinical Pharmacy Specialist on Antimicrobial Days of Therapy through Education Driven Policies, Procedures, and Interventions - Yolanda G. Martinez; MaiCuc Tran; Thomas Roduta; Susan Lam; Todd Price; Stefanie Stramel (MDPI AG, 2023)
The primary goal of antimicrobial stewardship is to improve patient outcomes and minimize the consequences of antibiotic use. Prospective audit and feedback cannot always be performed by an antimicrobial stewardship program member which is where policies, procedures and education can aid interventions. The purpose of this study was to evaluate the impact on antimicrobial days of therapy due to a dedicated clinical pharmacy specialist primarily responsible for developing policies and procedures and providing education. A pre-intervention and post-intervention retrospective analysis of antimicrobial days of therapy from September 2019-May 2020 and July 2020-March 2021 was performed. Inclusion criteria consisted of adults receiving IV vancomycin, azithromycin, meropenem, ciprofloxacin, and/or levofloxacin. Excluded criteria consisted of documented interventions that were not related to implemented policies and procedures or performed education and patients receiving antimicrobial surgical prophylaxis. The primary outcome was antimicrobial days of therapy. An average of 3.47 ± 2.46 days (pre-intervention, n = 203) and 3.21 ± 2.52 days (post-intervention, n = 203) were observed for the primary outcome (p < 0.04182). Pharmacists performed 75 interventions pre-intervention and 102 interventions post-intervention (p = 0.0092). The implementation of a dedicated antimicrobial stewardship clinical pharmacy specialist responsible for developing policies, procedures, and education successfully reduced antimicrobial days of therapy and documented interventions.